Comparison of Methods for Extraction of Infectious Influenza Virus from Raw Milk Cheeses - Madeleine Blondin-Brosseau; Wanyue Zhang; Caroline Gravel; Jennifer Harlow; Xuguang Li; Neda Nasheri (Journal of Food Protection)
In recent years, the highly pathogenic avian influenza (HPAI) H5N1 viruses have spread widely among birds and multiple mammal species. The HPAI spillover to dairy cattle, and its excretion in milk in high-titers has created a new interface for human exposure and has raised food safety concerns. Multiple lines of evidence show that pasteurization is effective in inactivation of influenza viruses. In Canada, dairy products must be pasteurized with the exception of cheese. Since influenza viruses were not considered as foodborne, there is no data available regarding their survival in cheeses and no standard method exists for their extraction from food commodities, including dairy products. Herein, we examined the efficacy of multiple methods for the extraction of infectious H1N1 virus (as a representative for type A influenza viruses) from cream cheese made from unpasteurized milk. We used murine norovirus (MNV) as a surrogate for human norovirus and also as a process control virus and examined the efficacy of the employed methods by plaque assay. The limit of detection for the two best-performing methods was determined using a variety of soft and firm raw-milk cheeses. The described methods assist health authorities for the surveillance of foodborne viruses in dairy products.